Factors contributing to late stillbirth among women with pregnancy hypertension in a developing country. (2nd July 2020) - Kumar, Manisha; Vajala, Ravi; Bhutia, PhunstokDoma; Singh, Abha
ABSTRACT: Objective: To investigate the factors associated with late stillbirth among women with hypertensive disorders of pregnancy (HDP). Material and Methods: The clinical details of women with HDP having late stillbirth were compared with controls having livebirth. Results: Total 208 cases and 288 controls were included in the study. Inadequate antenatal visits (p < 0.001, OR–5.92). birth weight < 2000 gms (p < 0.001, OR 10.3) and BW/PW ratio > 8 contributed significantly (p = 0.0001, OR-5.6) to stillbirth. Conclusion: Poor antenatal care, birth weight below 2000gms and high BW/PW ratio was associated with a higher risk of stillbirth.